Mechanisms of transcription: the eukaryotic pre-initiation complex - Hampsey, Michael (Henry Stewart Talks, 2007)
Overview of RNA polymerase II transcription, Core promoter elements, Proximal promoters, Enhancers and silencers, General transcription factors, Activators and repressors, Coactivator complexes, RNA polymerase II structure and function, Mechanisms of transcription initiation, Steroid hormone receptors, Chromatin remodellers including SWI/SNF, Covalent histone modifiers, including histone acetyltransferases, methyltransferases and deacetylases, Update interview: RNAP II carboxy-terminal domain (CTD), Update interview: Mediator complex, Update interview: Gene silencing, Update interview: Transcription termination, Update interview: Coupled transcription and mRNA processing, Update interview: Transcriptional memory
Updated at 2021/04/08